Effect of leverage, company growth and operating cash flow on bond ratings with firm size as moderation - Aditya, Yogga; Purwidianti, Wida; Tubastuvi, Naelati; Miftahuddin, Muchammad Agung (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of leverage, company growth and operating cash flow on bond ratings with firm size as a moderating variable. The type of research used is quantitative. Applies data from financial sector companies listed on the Indonesian Stock Exchange. Data collection method using purposive sampling method. There are 18 company objects during the 2016-2021 period so that 108 samples were obtained. The data analysis method uses interaction analysis, namely moderation regression analysis with the using of SmartPLS 3. The results of this research show that leverage has a negative impact on bond ratings. Company growth and operating cash flow have no impact on bond ratings. Firm size has a positive impact on bond ratings. Firm size can moderate the relationship between leverage and bond ratings. Firm size cannot moderate the relationship between company growth and bond ratings. Firm size cannot moderate the relationship between operating cash flows and bond ratings.